Jazz Arranging and Performance Practice: A Guide for Small Ensembles - Rinzler, Paul E. (Rowman & Littlefield Publishers, 1999)
Unlike most jazz arranging books, which focus on the rudiments of arranging (transposition, ranges, notation, and so forth), this book deals with the real substance of arranging for small jazz ensembles, in addition to the rudiments. Rinzler devotes a chapter to each of the following arranging elements: intros, endings, accents/breaks/dynamics, time and tempo changes, style changes, form, rhythm section procedure, harmony and orchestration. Over a hundred musical examples demonstrate arranging techniques that apply to 147 jazz standards and modern compositions.